(3GdNQGL hUfYI GdcJGHs - (3bOGeI Hf LYaQ Hf bOGeI Hf RjGO GdHZOGOj, CHh GdaQL,J (B337 (3g` s
(3ChdgG (B:s
(3Chdg GdefRdI GdKGefI GdHGH GdChd bGd GHh GdaQL bOGeI Hf LYaQ Cf Gddg JbOS hYdG deG Ndb GdGTjGA HbOQJg s
(3BNQgG (B:s
(3bO Je cJGH GdNQGL ai ZQg TgQ QHjY GdChd ai OGQ GdYdjI s
(3HgG fXGe GdJYbjHIs
(3hHChdg agQSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B191 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B128s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI SjFI s
Keywords: (3eJaQbGJs